Transforming Research Assessment for an Equitable Scientific Culture - Flores Bueso, Yensi (Septentrio Conference Series, 2023)
Watch VIDEO. Science plays a pivotal role in the advancement of democratic societies, and there is a growing consensus advocating for its recognition as both a common good and a fundamental human right. To effectively fulfil this role, science necessitates the trust of society, the support of policy makers, and robust international collaboration, enabling the mobility of researchers and the free flow of knowledge. To encourage this, our responsibilities as researchers extend beyond the realm of academic publishing. They encompass science outreach, education, diplomacy, policy advocacy, entrepreneurship, and collaborations aimed at addressing global challenges or progress towards more equitable societies. However, this is hampered by current research assessment practices and the academic reward system, which perpetuate a ’publish or perish’ research culture that confines the scope of science to academic publishing, fosters privilege-based biases, and prioritises quantity over quality, as well as prestige over integrity. During this talk, I will share my personal journey as an early career researcher from the Global South, now affiliated with one of the most innovative research labs worldwide. My research journey, which was enabled by securing highly competitive funding since early stages of my career, provided me with first-hand insight into the biases and repercussions of current research assessment practices on the trajectories of researchers. Further validating this perspective is a ground-breaking study I co-led with colleagues from the Global Young Academy, exploring research assessment for career advancement on a global scale. This study shows that research institutions worldwide heavily rely on bibliometrics to evaluate career progression, irrespective of the academic discipline. However, while more established institutions appear to be walking away from these practices, these are becoming more popular in emerging research institutions from low-middle income countries. These findings highlight the need for transformational global (inclusive) initiatives. I am privileged to be part of one such initiative – The Coalition for Advancing Research Assessment (CoARA). CoARA brings together a community of researchers and research enablers dedicated to reforming this perilous research culture. CoARA’s guiding principles centre on acknowledging the diversity of contributions and careers in science, shifting research evaluation towards qualitative aspects where research ethics and integrity are at the core, and recognizing that excellence is context-dependent, varying for each candidate, role, and projects. A standout feature of CoARA is its unwavering commitment to early career researchers, placing them at the heart of its principles, governance, structures, and interventions. Thus, ensuring that future generation of scientific leaders is well-equipped to navigate and transform the landscape of research assessment and scientific culture.